Optimization Model of Canal Blocking Performance in Block-C Region Ex. Peat Land Development-Center Borneo - Yakubson; Lily M. Limantara; Dian Sisinggih; Sumiadi (Journal of Human, Earth, and Future)
This study aims to optimize the performance of canal blocking in peatlands. Drought in peatlands increases the risk of fire disasters. Canal blocking is essential for reducing fire hazards and enhancing ecosystem health. Maintaining the water table height is key to managing peatland water levels and mitigating fire risks. The methodology involves simulating the hydraulic conditions of installed canal blocks using collected parameters. After conducting hydraulic simulations under existing conditions, further simulations were performed by varying the number and spacing of canal blocks to achieve a water level height close to the target of approximately ±0.6 meters. The simulation results show that in the branch canals, an additional 28 canal blocks are needed. However, in the main canal, the required number of blocks decreases significantly—from an initial 102 to just 30. Although this reduction is substantial, the minimum water level remains above the critical threshold. Optimization of canal blocking installation is achieved by prioritizing block placement at the dome outlet, specifically in the branch canals, to maintain water flow more efficiently.